Monopole Acoustic Logging While Drilling Acoustic Insulator Based on Labyrinthine Grooved Structure - DOU Yifan; ZHANG Chao; GUAN Wei (Cejing jishu)
In acoustic logging while drilling (ALWD), the presence of a thick-walled drill collar inspires significant amplitude drill collar waves, which will interfere with the measurement and acquisition of formation information. To address this issue, a novel acoustic isolator based on a labyrinthine grooved structure is proposed to effectively attenuate drill collar waves propagating along the drill string. The sound insulation performance of the proposed insulator is analyzed through both frequency-domain and time-domain responses. After parameter optimization, the labyrinthine grooved structure insulator consists of 10 grooved sections, each containing 20 random grooves along the circumferential direction. The results show that, within the sound source's central frequency range of 10~16 kHz, the structure presented in this paper has a good suppression effect on drill collar waves. Moreover, by using the proposed structure, formation P-wave and S-wave velocities can be derived by analyzing the array-received waveform data. Calculations demonstrate that the proposed structure meets the mechanical performance requirements under complex wellbore conditions. The findings of this study are expected to provide new insights for the design of sound insulators in ALWD and further enhance the accuracy of formation property acquisition in monopole ALWD.